2017
DOI: 10.3390/molecules22060898
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Gallic Acid Analogs as Histamine and Pro-Inflammatory Cytokine Inhibitors for Treatment of Mast Cell-Mediated Allergic Inflammation

Abstract: Gallic acid (3,4,5-trihydroxybenzoic acid), is a natural product found in various foods and herbs that are well known as powerful antioxidants. Our previous report demonstrated that it inhibits mast cell-derived inflammatory allergic reactions by blocking histamine release and pro-inflammatory cytokine expression. In this report, various amide analogs of gallic acid have been synthesized by introducing different amines through carbodiimide-mediated amide coupling and Pd/C-catalyzed hydrogenation. These compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Using both in vitro and in vivo experiments, we found that gallic acid regulates ILC2s via MyD88‐mediated IL‐33 expression, reducing IL‐5 and IL‐13 secretion of ILC2s and, consequently, improving pulmonary inflammation and AHR. Several studies have shown that gallic acid could function as an anti‐allergic agent in treating some allergic disorders, including asthma; however, to our knowledge, this is the first report showing that it may have anti‐asthma effects by regulating ILC2 activity.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Using both in vitro and in vivo experiments, we found that gallic acid regulates ILC2s via MyD88‐mediated IL‐33 expression, reducing IL‐5 and IL‐13 secretion of ILC2s and, consequently, improving pulmonary inflammation and AHR. Several studies have shown that gallic acid could function as an anti‐allergic agent in treating some allergic disorders, including asthma; however, to our knowledge, this is the first report showing that it may have anti‐asthma effects by regulating ILC2 activity.…”
Section: Discussionmentioning
confidence: 78%
“…As an effective anti‐inflammatory agent, gallic acid, or its synthetic analogs, has been found to inhibit release of histamine and pro‐inflammatory cytokines and also agonize G protein–coupled receptor‐35 (a proven target of asthma drugs such as cromolyn and nedocromil) . This limited evidence has suggested a possible role for gallic acid in asthma treatment, but few studies have been undertaken to test this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GA, a part of EGCG, was shown to have inhibitory effects on mast cell-mediated allergic inflammation in our previous studies, and we have generated various derivatives of GA to improve its pharmacological effectiveness (10,11). As mentioned above, to strengthen the effectiveness of GA, SG-SP1 was designed from GA (12). In this study, we aimed to compare the anti-allergic effects of SG-SP1 with those of GA.…”
Section: Discussionmentioning
confidence: 99%
“…The residue was purified by flash column chromatography on a silica gel (ethyl acetate/n-hexane = 1:3) to produce the desired amide. Compound 3d was identified as SG-SP1 (12).…”
Section: Synthesis Of Sg-sp1mentioning
confidence: 99%